(untitled) (FULafia Journal of Science and Technology, 2025)
This study was performed to compare the growth and survival rate of Oreochromis niloticus fry in different colours of plastic bowl (50 liters) for 10 weeks. Fry of O. niloticus (mean weight 0.08 g and body length of 0.53 cm) were stocked at 20 fish per bowl (white, red, black, green and blue bowls) in triplicates. They were fed with 45% Crude Protein Coppen feed at 5% body weight. Feeding was done twice daily, between 8 to 9 am and 4 to 5 pm. At harvest, the growth was significantly highest in black bowl but lowest survival of 52.7% (p<0.05). White bowl shows the highest survival rate of 91.3% but the fish camouflaged to the colour of the bowl (albino). Green bowl showed the best condition factor with survival rate of 89.40%. There was significant difference (p<0.05) in mean weight gain (8.62, 8.06, 8.45, 9.37 and 8.44) in white, red, green, black and blue bowls, respectively. The study concluded that the use of plastic bowl in culturing of fry is promising and economical, thereby reducing the cost of pond and tank construction.